Studi Putusan Hakim Nomor: 29/Pid.Sus/TPK/2018/PN.Jmb terhadap Pelaku Tindak Pidana Korupsi Pembangunan Embung di Desa Sungai Abang Kecamatan VII Koto Kabupaten Tebo Tahun 2015 - Muhammad Badri; Bambang Harianto (Universitas Batanghari Jambi, 2020)
Corruption crimes have increased from time to time, so it can be seen from the corruption cases that exist today, such as non-directive actors, both among the central government and regional governments. as happened in Tebo Regency in the construction of an embung. The biggest impact of this corruption crime can be a barrier to development in all fields, in this case, criminal sanctions are very much given as responsibility for the perpetrators of corruption. Regarding the imposition of a verdict on the perpetrator of corruption, a judge is required to know and be aware of the meaning of impeachment as well as to know and be aware of what he has accomplished, the purpose of imposing serious crimes in addition to providing deterrence for those who commit acts that are against the law, making people afraid to commit similar actions also to create a sense of community justice.